Resposta luteal à PGF2α (Dinoprost Trometamina) durante as fases de luteogênese e manutenção do corpo lúteo em éguas - Novaes Filho, Luiz Fernando [UNESP] (2014)
Recent studies have demonstrated different response of the CL to different doses of prostaglandin F2α on differente moments. The present experiment aims to evaluate the effect of treatments with PGF2α low doses over functional e structural characteristics of the CLs at two distintic stages. Mares were randomly assigned into groups: D2-NaCL (n=6; 2 mL of saline solution); D2-Pgf (n=9; 10 mg of Dinoprost Tromethamine); D2-1/10Pgf (n=6; 1 mg of Dinoprost Tromethamine); D2-1/20Pgf (n=6; 0,5 mg of Dinoprost Tromethamine); D8-NaCl (n=7; 2 mL of saline solution; D8-Pgf (n=6; 10 mg of Dinoprost Tromethamine); D8-1/10Pgf (n=7; 1mg of Dinoprost Tromethamine); D8-1/20Pgf (n=7; 0,5 mg of Dinoprost Tromethamine). Total area (AT), objective (PVO) and subjective (PVS) vascular perfusion of the CL and plasmatic progesterone (P4) were evaluated every six hours for 48h after treatment (H0 = immediately before treatment). PGF2α did not influenced on AT or day of treatment. P4 showed a positive correlation to PVO and PVS, and PVS was strongly correlated to P4. Treatment on D2 was not able to induce total luteolysis in any mare while treatment on D8 promoted total luteolysis in all mares in group D8-Pgf and 29% and 14% of the mares for the groups D8-1/10Pgf and D8-1/20Pgf, respectively. Parical luteolysis were also detected in groups on D8. The response to PGF2α seems to be dose-dependent, the decrease in PGF2α dose proportionally decreases PVS and P4. It is concluded that CL response to treatment with different doses of PGF2α depends os the CL developmental stage